Spectrophotometric Method for the Determination of Ciprofloxacin in Pure and Pharmaceutical Preparations: Development and Validation - Tariq Yassin Mahmoud; Isam Shaker Hamza; Aziz Latif Jarallah (Engineering Proceedings, 2024)
Ciprofloxacin (Cip) is spectrophotometrically identified through the formation of a colored charge-transfer complex that exhibits a maximum absorbance at 440 nm. This complex is generated by the reaction of the drug’s secondary amine with sodium nitroprusside (SNP) in an alkaline medium in the presence of hydroxylamine (NH2OH). Classical univariate analysis is employed to optimize the experimental conditions affecting the formation of the charge-transfer (CT) complex. The method presented herein offers a straightforward and sensitive approach for quantifying ciprofloxacin within a concentration range of 50.0–250.0 μg/mL. The method exhibits a molar absorptivity of 364.4817 L/mol·cm and a coefficient of determination (<semantics>r2</semantics>) of 0.997. Validation of the method is achieved through determination of the regression equation, accuracy, precision, and detection limit. The procedure is successfully applied to the quantification of ciprofloxacin in pharmaceutical formulations and demonstrates satisfactory recovery and precision. Statistical validation corroborates the reliability and repeatability of the obtained results.